Financial Sector Assessment Program Update : Philippines - Focused Update of the Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
This focused assessment of the current state of the Philippines' compliance with the Basel core principles for effective banking supervision is an update of the detailed assessment completed as part of the International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP) that took place in 2002. Thus, the current assessment targets those Basle Core Principles for Effective Banking Supervision (BCPs) for which the initial assessment was non-compliant or materially non-compliant, and those for which the FSAP had recommended reforms. As the original assessment had been made using the 1997 methodology, which was superseded by the 2006 methodology, the principles that were reviewed were mapped into the 2006 principles. This report should provide inputs for the enhancement of the Central Bank of the Philippines (BSP's) action plan to move toward full compliance with the core principles. This assessment of the effectiveness of banking supervision was based on an examination of the legal and regulatory framework and benefited from the inputs of the IMF resident advisor, as well as the BSP's very detailed self-assessment and responses to a questionnaire.